Why do policy leaders adopt global education reforms? A political analysis of SBM reform adoption in post-conflict Bosnia and Herzegovina - Komatsu, Taro (Education Policy Analysis Archives, 2013)
<span style="font-family: 'Garamond','serif'; font-size: 12pt; mso-bidi-font-size: 10.0pt; mso-fareast-language: EN-US; mso-fareast-font-family: 'ＭＳ 明朝'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">This paper presents a political analysis of school-based management reform in Bosnia and Herzegovina (BiH). School-based management (SBM), based on the principle of school autonomy and community participation, is a school governance system introduced in many parts of the world, including post-conflict nations. Such a phenomenon seems to follow the pattern predicted by the theories of institutional isomorphism. According to the institutionalists in comparative education, a country adopts global education reforms so as to enhance nation-building and nation-state legitimacy within the international community (Meyer, Boli, Thomas, & Ramirez, 1997; Ramirez & Boli, 1987). However, a closer look at the SBM reform adoption process in BiH reveals that, after legislating the global reform, policy leaders appear to have willfully derailed its implementation. Careful analysis of their legitimacy contexts suggests that BiH leaders may have adopted the internationally-driven reform policy primarily for the purpose of enhancing their precarious domestic legitimacy. Such behavior can be explained by Weiler’s (1983; 1990) political utility theory, which has not yet been sufficiently incorporated into the analysis of educational reform transfer. The study posits that policy leaders in reform-borrowing countries still play a crucial role in shaping education systems, even in the globalized world that is arguably driving these systems to converge. It is then important for comparative and international education scholars, as well as international donors, to critically assess the intent, practices and behaviors of the political leaders who accept global reforms.